Exploring the relationship between website quality and equity in living donor kidney transplant - McElroy, Lisa M.; Obayemi, Joy E.; Shaw, Brian I.; Park, Christine; Caddell, Keenan; Davis, LaShara A.; DePasquale, Nicole; Mohottige, Dinushika; Boulware, L. Ebony (Frontiers in Transplantation, 2024)
BackgroundHealth system websites are important resources to guide health care decisions and may be useful tools to improve racial equity in access to living donor kidney transplant (LDKT).MethodsWe performed a cross-sectional study of adult LDKT programs in the United States. We created an assessment tool for website quality across three domains: accessibility (access to LDKT specific information from the transplant center website), readability (ease of reading and clarity), and educational content (appropriateness and presentation of information, LDKT-specific content, program-specific characteristics, and adherence to equity-centered principles of web design).ResultsAmong the 185 transplant center websites reviewed, only 14.6% of LDKT sites could be accessed directly from the transplant center webpage. The median suitability assessment of materials (SAM)—a validated measure of website content for chronic kidney disease (CKD)—was 45 out of 86 (IQR 4) and the median Flesch-Kincaid grade level and ease score were 9.1 (IQR 0.8) on a scale of 0–18 and 51.2 (IQR 5) on a scale of 0–100, respectively.ConclusionThese results indicate that LDKT websites are currently not available, accessible, and understandable for many potential transplant candidates and donors. Optimizing the content and design of transplant center websites may be a promising and effective strategy for improving equity in access to LDKT.